Lipocalin-2 modulates recipients alloimmune responses to the murine kidney transplants - Pfefferkorn, Anna Maria; Fritsche-Guenther, Raphaela; Kusch, Angelika; Schwelberger, Hubert; Liu, Shiqian; Klopfleisch, Robert; Li, Yuhuan; Catar, Rusan; Liu, Shaokun; Aigner, Felix; Pratschke, Johann; Sauer, Igor Maximilian; et al. (Frontiers in Immunology, 2025)
BackgroundLipocalin-2 (Lcn2) is a sensitive early marker for acute kidney injury, delayed graft function and acute rejection of kidney transplants. We previously showed the renoprotective effect of recombinant Lcn2:Siderophore: Fe3+ (rLcn2) in a mouse kidney transplantation (KTx) model. Here, we investigate the molecular and cellular mechanisms underlying these effects.MethodsMale C57BL/6 mice (10–12 weeks) received BALB/c kidney allografts, with or without rLcn2 treatment (250 µg, s.c.). To examine the immunomodulatory function of rLcn2, immune cells from graft, spleen, lymph nodes and blood were analyzed by flow cytometry at post-operative days (pod) 3 and 7. Syngeneic C57BL/6 grafts were used to investigate the impact of rLcn2 on alloimmune-independent tissue injury and inflammation through multiplex signaling assays, functional readouts, cytokine profiling and histopathological analyses.ResultsrLcn2 treatment markedly reduced frequencies of distinct T cell subsets, including effector memory T cells and their cytotoxic (Tc) and helper (Th) subsets across grafts, lymphoid tissues and blood by pod-7 following allogeneic KTx. In graft infiltrating CD8+ T cells, rLcn2 decreased degranulation capacity and diminished expression of interferon-γ and perforin. rLcn2 also lowered the proportion of NKG2D+ CD8+ T cells, an activating Tc subset, in spleen and blood. In contrast, its impact on innate immune cells was modest and selective, influencing only neutrophils, macrophages in lymph nodes and intermediate mature NK cells in spleen and blood. No significant effect of rLcn2 treatment was observed on alloimmune-independent tissue injury or inflammation in syngeneic kidney grafts.ConclusionrLcn2 selectively modulates T-cell activity after KTx without affecting alloimmune-independent injury pathways.